Comment on "Consumption-based versus production-based accounting of CO2 emissions: Is there evidence for carbon leakage?". Issue 101 (November 2019) - Zhang, Qifeng; Fang, Kai
Highlights: Two databases used by the authors are incompatible and thus yield misleading results. There is distortion between the ranking by the ratio and by the distance. Data reanalysis shows serious carbon leakage from developed to developing countries. A complementary use of both metrics would be necessary to measure carbon leakage. Abstract: The authors should realize that the mixture of two incompatible databases—Emissions Database for Global Atmospheric Research (EDGAR) and Global Carbon Atlas (GCA) for production-based accounting (PBA) and consumption-based accounting (CBA), respectively, fails to examine carbon leakage from developed to developing countries in a meaningful way. By the authors' definition of carbon leakage, we calculate the ratio of CBA to PBA and the inconsistency index of national ranking where the data comes solely from GCA, and further compare the results with those provided by the authors. A striking difference has been witnessed not only in the ratio but also in the inconsistency index of national ranking. Our reanalysis of the data demonstrates that the ratio is an inherently poor measure of carbon leakage and that taking into account the distance between CBA and PBA can provide a more complete picture of carbon leakage that has become ubiquitous due to international trade.